Can children swallow tablets? Outcome data from a feasibility study to assess the acceptability of different-sized placebo tablets in children (creating acceptable tablets (CAT)). Issue 10 (10th October 2020) - Bracken, Louise; McDonough, Emma; Ashleigh, Samantha; Wilson, Fiona; Shakeshaft, Joanne; Ohia, Udeme; Mistry, Punam; Jones, Huw; Kanji, Nazim; Liu, Fang; Peak, Matthew
Abstract : Objective: Feasibility study to investigate the acceptability of different-sized placebo tablets in children aged 4–12 years. Design and setting: Clinical Research Facilities, inpatient wards and outpatient clinics within a Regional Paediatric Hospital and/or District General Hospital. Healthy children and National Health Service (NHS) patients were asked to swallow three placebo tablets: 6 mm, 8 mm and 10 mm, smallest to largest. The researcher observed children's facial expressions and behaviours on swallowing and measured the volume of water consumed. Participants completed a questionnaire about the overall acceptability; including swallowability, taste and volume of water consumed. For analysis, participants were stratified by age: 4–8 years and 9–12 years. Results: The feasibility study led to an estimated recruitment rate of 0.8% for NHS inpatients and 211 healthy children over a 1-year period. In total, 55 participants were recruited, 30 to the younger group, of which 77% had never taken a tablet before. 84% of the 25 older children had previously taken a tablet. All participants attempted to swallow the smallest sized tablet. The children aged 4–8 years found the larger tablets easier to swallow, however the older children found little difference between the tablet sizes. The younger children required more water to swallow each tablet size compared with the older children where an increasing volume of water was consumed as tablet size increased. Taste was rated highly for both age groups. The 8 mm tablets were deemed the most acceptable tablet size by all participants. Conclusion: Tablets are potentially an acceptable formulation for children aged 4–12 years. Most children aged 4–8 years who attempted to swallow tablets successfully did so. Recruitment of NHS inpatients to medicine acceptability studies is challenging, however, recruitment of children of staff proved an effective strategy. Valuable lessons have been learnt from this feasibility study which will inform the design of a larger definitive trial.